Optimization of AA5052 in incremental sheet forming using grey relational analysis. (August 2017) - Baruah, Angshuman; Pandivelan, C.; Jeevanantham, A.K.
Highlights: An effort has been made to understand the significant machining factors for the performance characteristics in Incremental sheet forming process. Lubrication has been identified as the highest contributing factor and the least contributing factor was feed. While using the multi objective optimization of Formability and Roughness, the Grey—Taguchi Method is most ideal and appropriate for ISF process. Abstract: In this paper, the main goal is to achieve enhanced formability and reduced surface roughness in Incremental Sheet Metal Forming (ISF) process in three directions – rolling, transverse and angular. This methodology combines Taguchi's orthogonal L9 array (3 4 ) for design of experiments, grey relational analysis and ANOVA. The experimental results verify that the suggested technique efficiently enhances the performance of ISF process. Lubrication has been identified as the highest contributing factor for all the three directions and feed rate as the least. Vertical step down and speed are the second and third contributing parameters.